Q12 A randomised feasibility study of a 12-week exercise programme in Huntington's disease (HD). (29th August 2012) - Busse, M; Quinn, L; DeBono, K; Jones, K; Collett, J; Playle, R; Kelly, M; Backx, K; Dawes, H; Rosser, A; ,; Backx, K; et al.
Abstract : Background: This multi-centre controlled study [ISRCTN 59910670 ] evaluated a 12-week exercise programme in mid stage HD in terms of adherence and potential benefit. Methods: 31 subjects (16 male) [mean (SD) age 50.4 (11.4) years and disease burden score (DBS) 438 (129)] were randomly allocated to intervention (n=16) or control (usual care) (n=15). Mean (SD) total functional capacity scores at baseline were 8.4 (2.6) and 8.9 (3.1) and mean (SD) Unified Huntington's Disease Rating scale total motor scores (UHDRS TMS) were 32.4 (15.5) and 35.2 (20.5) at baseline in the intervention and control respectively. The intervention was a weekly gym session and self-directed walking. Blinded assessments were conducted on a range of outcomes including the UHDRS modified motor score (UHDRS mMS), 30 s chair stand test (CST) and 6 min walk test. Results: Loss to follow-up was greater in those allocated to the intervention group (n=7; 5 never started the intervention) than those in the control (n=2). Median (range) gym attendance (n=9) was 9 (2–12) and mean (SD) weekly walking minutes was 247.5 (239.1). There were no related adverse events. No significant differences were seen at follow-up (controlling for baseline age, gender, DBS and physical activity scores) on the UHDRSmMS (difference between groups adjusted for baseline scores (2.41, 95% CI −0.93 to 5.75); CST (1.28, 95% CI [−1.2 to 3.8]) and 6 min walk (27.2 95% CI [−2.8 to 57.2]). Conclusion: Clinical benefit is not clearly demonstrable in this small study, however it is encouraging that there were no related adverse events and that good gym attendance rates were achieved. Data gathered in this study can inform planning of future trials of exercise interventions in HD.